Implementation of School Supervisory Academic Supervision as an Effort to Increase Teacher Performance in Junior High School - Nurwati Nurwati; Kaharuddin Kaharuddin; Erwatul Efendi; Masruddin Masruddin (State Islamic Institute of Palopo, 2021)
This study aims to describe the implementation of the academic supervision of school supervisors as an effort to improve teacher performance at SMP Negeri 3 Palopo. To find out the implementation of academic supervision carried out by school supervisors related to teacher performance, to know the supervision model that can improve teacher performance, to know the improvement of teacher performance as the impact of academic supervision at SMP Negeri 3 Palopo. This research is a qualitative research that describes the data according to what is happening in the field. The approach used is managerial. The approach in this management perspective is planning, organizing, implementing, monitoring, and evaluating. Sources of data are primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. Analysis of the data used is data collection, data reduction, data presentation, drawing conclusions. The results showed that the implementation of the supervision of school supervisors in improving teacher performance at SMP Negeri 3 Palopo went through three stages, namely the planning stage, the implementation stage, and the advanced stage. The supervisory model of school supervisors in improving teacher performance at SMP Negeri 3 Palopo uses several supervision models, namely the scientific supervision model, the artistic supervision model, and the clinical supervision model. However, in general, school supervisors use a clinical supervision model to observe the learning process directly. The impact of the implementation of academic supervision by school supervisors has a positive impact on teachers both in terms of learning administration, as well as from the learning process, of course, it is very influential on student learning outcomes and improving teacher performance at SMP Negeri 3 Palopo.